2011
DOI: 10.2176/nmc.51.515
|View full text |Cite
|
Sign up to set email alerts
|

Neuroendoscope-Assisted Removal of an Organized Chronic Subdural Hematoma in a Patient on Bevacizumab Therapy-Case Report-

Abstract: A 78-year-old Japanese man with a history of colon cancer was referred to our department of neurosurgery for the management of asymptomatic left chronic subdural hematoma (CSDH). He was receiving bevacizumab therapy for colon cancer, and the size of the CSDH increased or decreased depending on bevacizumab administration. Simple drainage was performed because of the risk of a critical increase in the size of CSDH during bevacizumab therapy, but since the CSDH was organized and firm, the drainage was insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 14 publications
(19 reference statements)
0
16
0
Order By: Relevance
“…Bevacizumab is a monoclonal antibody used in the treatment of certain cancer types because of its action on vascular endothelial growth factor [8]. Several links between bevacizumab and central nervous system hemorrhage have been reported.…”
Section: Bevacizumabmentioning
confidence: 99%
See 2 more Smart Citations
“…Bevacizumab is a monoclonal antibody used in the treatment of certain cancer types because of its action on vascular endothelial growth factor [8]. Several links between bevacizumab and central nervous system hemorrhage have been reported.…”
Section: Bevacizumabmentioning
confidence: 99%
“…Several links between bevacizumab and central nervous system hemorrhage have been reported. Takahashi et al [8] reported a case of a 78-year-old patient with colon cancer who was treated with an undescribed chemotherapeutic and bevacizumab and was found to have a chronic SDH on a follow-up PET scan. The patient underwent burrhole drainage initially, but after the hematoma failed to drain, it was evacuated.…”
Section: Bevacizumabmentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] In contrast, hyperostosis is a common consequence of adjacent or invasive meningiomas. However, the uncommon thickening of the skull indicated a complication.…”
Section: Meningioma Mimics Chronic Subdural Hematoma: a Case Report Amentioning
confidence: 99%
“…[1][2][3][4] OCFs can easily be missed because of their highly variable and usually nonspecific clinical features. On account of a greater awareness and widespread use of computed tomographic (CT) scanning, OCF is being reported more frequently.…”
Section: Doimentioning
confidence: 99%